Implementing Remote Procedure Calls - Birrell, Andrew; Nelson, Bruce Jay (ACM Transactions on Computer Systems, 1984)
Remote procedure calls (RPC) appear to be a useful paradigm for providing communication across a network between programs written in a high-level language. This paper describes a package providing a remote procedure call facility, the options that face the designer of such a package, and the decisions we made. We describe the overall structure of our RPC mechanism, our facilities for binding RPC clients, the transport level communication protocol, and some performance measurements. We include descriptioro of some optimizations used to achieve high performance and to minimize the load on server machines that have many clients.